RESEARCH ON SMART EDUCATION - Чайковская, Ольга (SWorldJournal, 2021)
The present paper aims at determining the main characteristics of smart education. Literature review showed that smart education is an effective, self-directed, motivated, adaptive, resource-enriched, and technology-embedded type of learning. The devices,